RESULT ORIENTED PLANNING AS A TOOL OF THE STATE INNOVATIVE POLICY - A. Ivanov; O. Kuznetsov (Управленческие науки, 2015)
The article considers the preconditions stipulating the necessity of transition to result oriented planning and its role and importance in the process of budget forming and implementing is reasoned as well. The result oriented planning is investigated as a tool of innovative policy carried out through the analysis the implementing of the state program “Economic development and innovative economy”.The scientifi article gives the all-round analysis of federal legislation and decrees of the President of the Russian Federation on the problems of the result oriented planning in the Russian Federation allowing to provide the implementing the result oriented planning as a tool of the state innovative development. The results of comparative analysis of domestic and foreign experience in implementing the Government program “Economic development and innovative economy” are presented”. Based on the results of comparative analysis the main problems in the fi of economic development and innovative economy are exposed, as well as the factors which can substantially influence on the results of the state innovative policy. The practical importance of basic measures of the preliminary Government program is grounded, namely: providing the co-ordination of innovative policy; maintenance the innovative projects at the state level, which are connected with the creation and functioning of technological platforms; implementing the Complex program of development of biogeotechnologies for the period until 2020; stimulation of innovations in companies with state participation; creation and development of institutes and infrastructures, providing start and work of innovative projects at all stages of the development; creation the centers of innovative development etc. Based on the investigation results the conclusions and recommendations are formulated concerning the improvement of result oriented planning and introduction the innovative economy.